Electronic and Photonic Packaging, Electrical Systems and Photonic Design, and Nanotechnology 2003
DOI: 10.1115/imece2003-41844
|View full text |Cite
|
Sign up to set email alerts
|

Test Methodology for Impact Testing of Portable Electronic Products

Abstract: This paper introduces a test methodology to examine the durability of surface mount interconnects under impact loading when a portable electronic product is dropped. Conventional testing approaches that consider loading (total impact energy, orientation and number of impacts) as the governing criterion for failure, typically report difficulties in correlating with impact durability under field conditions. This study considers damage accumulated in the interconnects in terms of local flexural strain, strain rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…7b). Varghese et al [32,33] of CALCE delivered the impact using a steel ball attached to a string (Fig. 7c).…”
Section: Ic Componentmentioning
confidence: 97%
See 2 more Smart Citations
“…7b). Varghese et al [32,33] of CALCE delivered the impact using a steel ball attached to a string (Fig. 7c).…”
Section: Ic Componentmentioning
confidence: 97%
“…Varghese et al [32,33] of CALCE proposed a fatigue damage model that takes into account the bending mode and the stress amplitude. Discrete wavelet transform techniques were used to decompose the time history response of the PCB obtained from impact bending tests (Fig.…”
Section: Damage and Failure Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…PWB flexure is a primary cause of electronic product failures (9). Therefore, the product should be designed so that impacts or shocks to the exposed portions of the product result in minimal deformation of the internal PWBs.…”
Section: Load Path Managementmentioning
confidence: 99%
“…Tests conducted by Yu et al [7] and Juso et al [8] indicated that the number of cycles to failure decreased as the PWA strain and strain rate increased. Varghese and Dasgupta [9] ran impact tests on PWAs in the in-plane and out-of-plane orientations and showed that the number of impacts to failure decreased with increasing PWA strain. The failure site for both impact orientations was the interfacial intermetallic layer.…”
Section: Introductionmentioning
confidence: 97%